POTENSI EKONOMI DAERAH DALAM PENGEMBANGAN UKM UNGGULAN DI KABUPATEN SEMARANG - Rusdarti, R (JEJAK: Jurnal Ekonomi dan Kebijakan, 2010)
The purpose of this study was to describe the phenomenon of SMEs superior and superior product, superior type of SMEs superior product and formulating policy strategy, in accordance with hte potential of SMEs in Ungaran, Semarang Regency. This research was conducted using the method of documentation with secondary data from the books in BPS and Bapeda Semarang Regency period 2004-2008. Method of assessment approaches and processes to find different types of SMEs and excellent potential in these areas would use a SWOT analysis method and Location Quotient (LQ).The results showed that: (1) Potential sectors that could be driving the manufacturing sector, in terms of small scale industries (SMEs) is a type of food and beverage industry, and traditional medicines. Processing industry is a sector basis and the biggest contributor to economic growth in the district of Semarang. Potential sectors that could be driving the manufacturing sector, in terms of small scale industries (SMEs) is a type of food and beverage industry, and traditional medicines. Processing industry is a sector basis and the biggest contributor to economic growth in the district of Semarang. (2) Policy strategy that can be applied based on the SWOT analysis are: (a) Strength Strategy Opportunity (SO), local product development, utilization of water resources potential to be a mineral water companys industrial sector, (b) Weakness Opportunity Strategy (WO), to realize the industrial area which mengutakan local raw materials such as: industry tempeh, tofu, crackers, chips and other variations that do not rely on raw materials imported from abroad. Utilizing the barren land to build industrial park, (c) Strategy Treath Strength (ST), the industrial sector become a leading sector, cooperation with other regions in pemanfataan pemanfataan water resources and tourist villages, and (d) Strategies Treath Weakness (WT), improve facilities and infrastructure, improving workforce skills for small industries to maintain and or improve the quality of its products.It is suggested local goverment should remain small support industry to remain a leading sector in a way makes it easy for small industry in the necessary permits and acces capital and marketing and increasing skill of its workforce.Â